TINJAUAN KONSTRUKSI BANGUNAN RUMAH TINGGI DI KAMPUNG ARAB AL-MUNAWAR PALEMBANG - Widi Dwi Satria (Nature : National Academic Journal of Architecture, 2022)
Indonesia is a country that has traditional houses in almost every province. The architecture of traditional houses in Indonesia is identical to houses that use local materials obtained from the natural surroundings. The durability of the structure and construction of traditional houses is an essential concern, considering the materials used are constantly being consumed by the times. Rumah Tinggi is part of the typical Palembang pyramid house with the use of materials that are dominated by wood. Rumah Tinggi still survives today during the progress of the times. The review of high-rise construction is interesting to study considering the age of the building is more than 250 years, with occupants from the 7th generation. The research is located in the Arabian village of Al-Munawar, Palembang, with the object of Rumah Tinggi. The method used is qualitative with an observation and interview approach. This study aims to identify the existence of traditional houses called high houses against the development of the times. The study results show that using wood materials still dominates the structure and construction of Rumah Tinggi. Rumah Tinggi still survives to this day. Residents of the house still apply building maintenance by replacing damaged wood components and paint to rejuvenate the atmosphere of Rumah Tinggi. Adjustments in high houses do not fade the authenticity and characteristics of Rumah Tinggi.